2020
DOI: 10.3390/antiox9100972
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Synthetic Cationic Iron Porphyrins

Abstract: Widespread antibiotic resistance demands new strategies for fighting infections. Porphyrin-based compounds were long ago introduced as photosensitizers for photodynamic therapy, but light-independent antimicrobial activity of such compounds has not been systematically explored. The results of this study demonstrate that synthetic cationic amphiphilic iron N-alkylpyridylporphyrins exert strong bactericidal action at concentrations as low as 5 μM. Iron porphyrin, FeTnHex-2-PyP, which is well tolerated by laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The study results correspond to the well-known fact that a certain number of peripheral blood granulocytes contains substances responsible for oxygen-dependent (Smirnova et al 2018) (spontaneous NBT test (Fig. 1-1) and oxygen-independent (Tovmasyan et al 2020) (cationic proteins (Fig. 1-3) bactericidal activity (Tohyama et al 2019).…”
Section: Discussionsupporting
confidence: 86%
“…The study results correspond to the well-known fact that a certain number of peripheral blood granulocytes contains substances responsible for oxygen-dependent (Smirnova et al 2018) (spontaneous NBT test (Fig. 1-1) and oxygen-independent (Tovmasyan et al 2020) (cationic proteins (Fig. 1-3) bactericidal activity (Tohyama et al 2019).…”
Section: Discussionsupporting
confidence: 86%
“…6) were compared, testing the influence of the alkyl's length chain on E. coli disinfection, where it was found that the compound 20, bearing an alkyl chain with eight carbons, decreased the bacterial viability in around 97%, while compound 17 was only able to reduce bacterial viability by 20% [43,44] . These results were compared with similar iron(III)-metalated porphyrins [45] , obtaining similar results and bearing the same conclusions: for Gramnegative inactivation not only charges are needed but also lipophilicity is desirable. Then, we could hypothesize that the cationic charges ensure a tight interaction with the negatively charged LPS, while the lipophilicity ensures the penetration through the two cellular membranes; then, a highly cationized molecule could be bound tightly to the outside of the cell, preventing its internalization and preventing its photodynamic effect, as ROS are unable to diffuse through the bacterial envelope.…”
Section: Cationic Porphyrinsmentioning
confidence: 61%
“…As photodynamic applications against microorganisms gain popularity, researchers are likely to seek for alternatives away from already established research lines, diversifying the photodynamic systems used.PS We have previously addressed several metals, such as iron [45] , iridium [60], palladium [39] , ruthenium [54] , and lutetium [52] , are used to form complexes with PSs. However, the use of metals is not limited to the decoration of already established PSs, and in the following sections we will present several examples where metallic complexes permit the formation of efficient photosensitizing systems.…”
Section: Synthetic Metallic Complexesmentioning
confidence: 99%
“…The magnetic properties of Fe(TPP)Cl are good enough for biomedical and therapeutic application [ 54 ]. It is antimicrobial active against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli [ 55 ]. Fe(TPP)Cl has low toxicity to eukaryotic cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%